American Medical Association, Report of the Board of Trustees - Correspondence: Glasson to Estes - Glasson, John (1973)
Correspondence from John Glasson, MD, North Carolina Medical Society, to E. Harvey Estes, Jr., MD, Chair of the Department of Community Health Services, Duke University Medical Center, indicating that report to Board of Trustees had been filed pertaining to earlier Resolution 41 passed by the AMA's House of Delegates in 1972. The Report and the Resolution are attached. The Report expresses concern that passage of Resolution 41 overly encourages undue proliferation of new physician support occupations in medical and surgical subspecialties limiting the education and scope of practice of these specialty-trained PAs. It was recommended that the development and training of new assisting occupations be coordinated for the various specialties through a meeting of all these groups.